2003
DOI: 10.1523/jneurosci.23-13-05607.2003
|View full text |Cite
|
Sign up to set email alerts
|

Categorically Distinct Acute Stressors Elicit Dissimilar Transcriptional Profiles in the Paraventricular Nucleus of the Hypothalamus

Abstract: The paraventricular hypothalamic nucleus (PVH) is a key site for integrating neuroendocrine, autonomic, and behavioral adjustments to diverse homeostatic challenges, including "physiological" (e.g., infection or hemorrhage) and "emotional" [e.g., restraint (RST) or footshock] stresses. Both types of challenges ultimately converge to activate common response systems represented in PVH, including the hypothalamo-pituitary-adrenal axis and the sympathoadrenal system. Oligonucleotide microarrays (U74A; Affymetrix,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
86
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 59 publications
(51 reference statements)
12
86
1
Order By: Relevance
“…7). These results are consistent with the observation that high-arousal states, including stress, are associated with elevated hypocretin neurotransmission (Espana et al, 2003) and that acute stress increases levels of hypocretin mRNA (Reyes et al, 2003). A metabolic challenge (i.e., fasting) induces a robust activation of both hypocretinergic neurons and the postsynaptic targets of hypocretinergic axons , although this effect may also be attributed to stress.…”
Section: Discussionsupporting
confidence: 90%
“…7). These results are consistent with the observation that high-arousal states, including stress, are associated with elevated hypocretin neurotransmission (Espana et al, 2003) and that acute stress increases levels of hypocretin mRNA (Reyes et al, 2003). A metabolic challenge (i.e., fasting) induces a robust activation of both hypocretinergic neurons and the postsynaptic targets of hypocretinergic axons , although this effect may also be attributed to stress.…”
Section: Discussionsupporting
confidence: 90%
“…Other chemokines such as MCP-1/CCL2 and growth-related gene alpha (GROa/ CXCL1) demonstrate a LPS responsiveness. Indeed, an up-regulation of MCP-1/CCL2 transcription is detected in the choroid plexus, CVO, blood vessels, and meninges (Thibeault et al 2001, Reyes et al 2003. GROa/CXCL1 also exhibits an up-regulation of its transcription in the PVN and the choroid plexus but not in the CVO (Reyes et al 2003).…”
Section: Chemokines and Stressmentioning
confidence: 99%
“…Thus, IL-8/CXCL8 could be a component of a stress-related neuroendocrine system (Licinio et al 1992). Moreover, after a noxious stimulation consecutive to a s.c. injection of bacterial lipopolysaccharides (LPS), an up-regulation of CINC and interferon g-inducible protein (IP-10/ CXCL10) mRNAs expression was found in the PVN (Sakamoto et al 1996a, Reyes et al 2003. In addition, it was observed that IP-10/CXCL10 expression is also up-regulated following LPS in the circumventricular organs (CVO) including the subfornical organ (SFO) and the area postrema.…”
Section: Chemokines and Stressmentioning
confidence: 99%
“…Several recent microarray studies examined the effects of the high-affinity GR agonist dexamethasone on human PBMCs and found that amidst expected anti-inflammatory changes in gene expression, there were many proinflammatory systems such as chemokines, compliment proteins, and cytokines with increased expression (Galon et al 2002;Reyes et al 2003). The following section reviews several representative situations where acute GCs enhance peripheral inflammation, but is by no means comprehensive.…”
Section: The Pro-inflammatory Effects Of Gcs Outside the Nervous Systemmentioning
confidence: 99%